218k views
2 votes
Add the equations.

5x - y = - 1
+-5x + 3y = 25

Add the equations. 5x - y = - 1 +-5x + 3y = 25-example-1
User Tiffiany
by
5.4k points

2 Answers

6 votes

C

Add the like terms from both equations on both sides

(5x - 5x ) + (- y + 3y ) = - 1 + 25

0 + 2y = 24

2y = 24 → C


User Praveen VR
by
6.0k points
1 vote

Answer:

C. 2y = 24

Explanation:

The sum of x-terms is 5x + (-5x) = x(5 -5) = 0.

The sum of y-terms is -y +3y = y(-1+3) = 2y.

The sum of the constant terms is -1 +25 = 24.

The result is ...

... 2y = 24

User Pouzzler
by
5.0k points